Creating cultures of thinking the 8 forces we must master to truly transform our schools - Ritchhart, Ron (Jossey-Bass, 2015)
"Discover why and how schools must become places where thinking is valued, visible, and actively promoted. As educators, parents, and citizens, we must settle for nothing less than environments that bring out the best in people, take learning to the next level, allow for great discoveries, and propel both the individual and the group forward into a lifetime of learning. This is something all teachers want and all students deserve. In Creating Cultures of Thinking: The 8 Forces We Must Master to Truly Transform Our Schools, Ron Ritchhart, author of Making Thinking Visible, explains how creating a culture of thinking is more important to learning than any particular curriculum and he outlines how any school or teacher can accomplish this by leveraging 8 cultural forces: expectations, language, time, modeling, opportunities, routines, interactions, and environment. With the techniques and rich classroom vignettes throughout this book, Ritchhart shows that creating a culture of thinking is not about just adhering to a particular set of practices or a general expectation that people should be involved in thinking. A culture of thinking produces the feelings, energy, and even joy that can propel learning forward and motivate us to do what at times can be hard and challenging mental work"-- Provided by publisher.